E-cigarette device and liquid characteristics and E-cigarette dependence: A pilot study of pod-based and disposable E-cigarette users. (January 2022) - Do, Elizabeth K.; O'Connor, Katie; Perks, Siobhan N.; Soule, Eric K.; Eissenberg, Thomas; Amato, Michael S.; Graham, Amanda L.; Martin, Corby K.; Höchsmann, Christoph; Fuemmeler, Bernard F.
Highlights: Power, nicotine concentration, and nicotine flux differ by device type. Nicotine flux is predictive of dependence among pod-based users. Age and past 30-day use were associated with nicotine dependence. Abstract: Background: E-cigarette device and liquid characteristics, such as electrical power output and liquid nicotine concentration, determine the rate at which nicotine is emitted from the e-cigarette (i.e., nicotine flux), and thus are likely to influence user nicotine dependence. We hypothesize that nicotine flux would be associated with the E-cigarette Dependence Scale (EDS) among pod-based and disposable e-cigarette products. Methods: Data were obtained from online panel participants between 18 and 65 years of age, who had indicated that they were either former or current e-cigarette users and resided within the United States (N = 1036). To be included in these analyses, participants had to provide information regarding device type (pod-based or disposable), power (watts), and nicotine concentration (mg/mL), from which we could determine nicotine flux (µg/s) (N = 666). To assess the relationship between nicotine flux and EDS, a series of multivariable linear regressions were conducted. Each model was separated by device type and adjusted for by age and past 30-day e-cigarette use. Results: Greater nicotine flux was associated with higher EDS scores among pod-based e-cigarette users (beta = 0.19, SE = 0.09, p-value = 0.043), but not users of disposable e-cigarettes. Neither power nor nicotine concentration were associated with EDS scores among users of either e-cigarette device type. Conclusion: Results support the hypothesis that nicotine flux is positively associated with nicotine dependence in a sample of current users of pod-based and disposable e-cigarettes.